Hypobiosis and Development of Haemonchus contortus and Trichostrongylus colubriformis Infection in Lambs under Different Levels of Nutrition - Carvalho, Nadino; Neves, José Henrique das [UNESP]; Pennacchi, Caio Santos [UNESP]; Amarante, Alessandro Francisco Talamini do [UNESP] (MDPI, 2023)
The influence of four levels of dietary supplementation on the development of the immune response and on the biology of Haemonchus contortus and Trichostrongylus colubriformis was evaluated in Dorper lambs under serial artificial infections with 1000 infective larvae (L3) of each species; the supplement was given every 3 days for 12 weeks. For each of the four diets formulated, one infected group (n = 7) and one control group (n = 4) were set up. Diets 1, 2, 3, and 4 contained 0%, 25%, 50%, and 75% of concentrate, respectively. There was an evident immune response to infection in all groups, manifested through eosinophilia and the production of anti-L3 immunoglobulins. There was a significant inverse relationship between the levels of nutrients in the diets and the numbers of late fourth-stage larvae, immature adult stages, and adults of H. contortus. Following 12 weeks of serial infections, most of the H. contortus population was found at the early fourth stage, indicating the occurrence of hypobiosis. The early fourth stage represented 59.5%, 75.8%, 83.3%, and 86.3% of the total Haemonchus worm burden, respectively, in Diets 1, 2, 3, and 4. In the case of T. colubriformis, hypobiosis was not observed, and diet had no influence on the establishment of parasites.
Keywords: eosinophils; epidemiology; immune response; nutrition; sheep